Multiple lead underwriter IPOs and firm visibility - Jeon, Jin Q.; Lee, Cheolwoo; Nasser, Tareque; Via, M. Tony (Journal of Corporate Finance, 2015)
One of the primary goals of a firm going public is to create a greater visibility to investors in general. Using a sample of 809 IPOs from 2001–2010, we empirically examine and find that multiple lead underwriters (MLUs) have greater visibility through our five pre- and post-IPO visibility measures. This also holds after accounting for potential endogeneity. Also, MLU-IPOs do not have more underpricing. Our results suggest that issuers with MLUs can increase the firm’s familiarity to the investment community and expand their investor base, and this increased firm visibility is not a trade-off for a greater level of underpricing.